Equivalents of Phraseological Units with the Cardinal Numeral Component in The Italian and English Languages - Khudaykulov Bekhzod (Periodica Journal, 2022)
This article is devoted to the study of phrase logical units on the basis of a comparison of the phraseological units of the Italian and English languages. The research represents the comparative description of the phraseological units with the cardinal numeral component of Italian and English languages. The phraseological equivalence is shown in the examples of compared meanings of phraseological units. Theoretical data about phraseological units are discussed and analyzed with reasonable examples.
Keywords: reasonable; Phraseology; idioms; translation